Landscape and Gods among the Khanty - Art Leete (Journal of Ethnology and Folkloristics)
The purpose of this article is to examine Khanty spatial ritual behaviour in the context of the simultaneous application of different ideas about sacred landscape. I aim to demonstrate the functional pattern behind handling seemingly ambivalent characteristics of cosmological models in the tangible ritual performance of the Khanty, an indigenous people inhabiting the taiga and forest taiga zone of Western Siberia. I explore three cases in which the concept of sacred topography is applied among the Khanty by exploring two public ceremonies of reindeer sacrifice and one episode of a post-funeral rite. It appeared that the spatial conceptualisation is different in different rituals. During sacrificial ceremonies, the Khanty position the Upper World in the southern direction, while in the case of death rituals, the Upper World is projected towards upstream of a river, even if it remains in the north. Studying different spatial orientations during rituals may provide a methodological key for approaching other concepts of vernacular belief among Siberian indigenous communities.